Komunikasi Interpersonal Pelatih dalam Meningkatkan Prestasi Atlet Esports Lokapala Sumatera Utara - Siahaan, Michael Yohannes; Selamat Riadi (Majalah Ilmiah METHODA, 2025)
This study aims to understand the role of the coach’s interpersonal communication in shaping motivation and enhancing the performance of Lokapala Esports athletes in North Sumatra Province. A qualitative approach was employed using in-depth interviews and observations involving the coach and six athletes from diverse ethnic backgrounds, namely Batak, Tamil, Chinese, Malay, and Javanese. The findings indicate that the coach's intensive interpersonal communication—both technical and motivational—significantly impacts the team’s enthusiasm and coordination. Interactions grounded in empathy, emotional closeness, and openness help create a conducive training environment. This study also highlights how cultural diversity within the team does not pose a barrier but instead becomes a strength through the coach’s inclusive and relationship-oriented communication strategies.